An equilibrium model of tax abatement: city and firm characteristics as determinants of abatement generosity - Byrnes, Patricia; Sridhar, Kala; Marvel, Mary K. (1999)
The model of tax abatements includes taxing district and form characteristics to explain a locality's abatement generosity. The community-level characteristics are for the school district in the enterprise zone that grants the tax abatement. Firm characteristics include the size, credit rating, number of newly created and/or retained jobs, and the quality of the jobs. Generosity of abatements is measured by the percentage of taxes abated. Firms that had credit ratings showing them to be more suitable risks fared better in negotiations; those that brought newly created jobs garnered more generous abatements; and those that promised retained jobs in the negotiation fared less well. - Reproduced
Keywords: Tax remission; Taxation